Інтернет-ресурси та католицька церква - Добродум, О. (Спеціальні історичні дисципліни: питання теорії та методики, 2009)
В статье исследуется проблема возрастающей роли электронных средств массовой информации в современной религиозной жизни (кибер-конфликты и кибер-войны, Интернет-аукционы и Интернет-сервисы, компьютерные вирусы и спам, биометрия, киберсквоттерство и пр.), характеризуется феномен виртуализации в католицизме. The article covers the issue of the impact of electronic mass media in the modern religious life (cyber-conflicts and cyber-wars, Internet-auctions and Internet-services, computer viruses and spam, biometria and cybersquatting, etc). The article also provides analysis of the virtualization phenomenon in Catholicism.